Getting started : technopreneurship in Singapore. - Chua, Chze Koon. (2008)
The entrepreneur of a technology startup faces many challenges and must overcome numerous obstacles in the harsh business world. Like Tarzan of the Apes, he must survive in the techno-jungle fighting off fierce competitions, protecting and expanding his turf. By swinging from tree to tree, occasionally falling off, he learns the ropes of management in business strategy, resource planning, technology, marketing, innovation and creativity, legal framework, political environment, and financial management in creating and sustaining a techno-startup.